Land, Men, Taxation - An Application to Pre-Modern China and Europe: Erik Jones' European Miracle Revisited - Charles B. Blankart (Center for Economic Studies and ifo Institute (CESifo), 2014)
Eric Jones has found that excessive taxes were detrimental for pre-modern China's economic growth whereas moderate taxes were conducive for Europe's economic growth. This paper provides a political-economic answer to the question why these two tax systems came about. Taxation is only feasible when men and land can be linked as a single bundle. Taxation of land is not feasible without men, and taxation of men is not feasible without land. A tax maximizing bureaucrat has to combine the two variables in such a way that tax revenues are maximized given the constraints of land and men in his country. China's contiguous geography allows bureaucrats to establish an autocratic tax system whereas Europe's split geography enforces a competitive tax system. Therefore often contiguous states reveal to be stable states whereas split states turn out to be unstable and prone to collapse.
Keywords: H20; N40; P50; 330; land; population; taxation; autocracy; multipower system; Great Divergence debate